Diseño de una estrategia para la detección y caracterización de nuevos genes asociados al proceso de inestabilidad genómica (2017)
The genomic evolution has remained in a fine balance between stability and change. The accumulation of massive variations over a short periods of time compromises cellular homeostasis, on the other hand, a few changes